Corruption and Stock Market Development: Evidence from Asian Countries - Lee, Kelvin Yong Ming; Mohamad, Jais; Rossazana Ab-Rahim, Ab-Rahim; Ayoib, Che-Ahmad (Academic Research Publishing Group, 2018)
Stock market plays a significant role in corporate financing. However, stock market movements were highly affected by certain external factors such as economic, psychological and political factors. By using the sample of 10 Asian countries, this study intends to investigate the impacts of macroeconomic and corruption factors on the stock market development. The sample period covered from the year 2003 to 2015. The dependent variable used in this study was stock market development. Whilst, the variables of interest used in this study were i) income level, ii) savings, iii) foreign direct investment, iv) value of stocks traded, v) money supply and vi) corruption perception index (CPI). A panel data approach had been applied in testing the relationship between the variables due to the nature of data. As expected, the gross domestic savings, foreign direct investment, and money supply were found to have a significant relationship with stock market development. On the other hand, the income level found to have a significant negative relationship with the stock market development. Noteworthy, the results also indicated that lower corruption level could lead to the growth of stock market development. Thus, a change in corruption level was the important matter to be considered before making any investment decision as corruption level had a significant impact on the stock market development.